The effect of entrepreneurial readiness, adversity quotient, and social intelligence on employability students - Zulmi, Nizar; Tentama, Fatwa (Intelektual Pustaka Media Utama, 2024)
Vocational high schools aim to create graduates who are ready to work, but in reality, many graduates are not ready to work at this time. Low employability is the main problem. This study aims to design and test a theoretical model of the effect of entrepreneurial readiness, adversity quotient, and social intelligence on employability in vocational high school students. The population of this study was students of class XII vocational high school